PENGARUH LIRIK LAGU “FORTUNE COOKIE YANG MENCINTA” TERHADAP PERSEPSI HUBUNGAN CINTA PENGGEMAR JKT48 DI KOTA BANJARBARU - Roza, M Fathor; Ayuni, Risa Dwi; Puspita, Amelia (KAGANGA KOMUNIKA: Journal of Communication Science, 2025)
This study investigates the influence of the song lyrics “Fortune Cookie yang Mencinta” on the perception of romantic relationships among JKT48 fans in Banjarbaru. JKT48 is an Indonesian idol group widely popular among teenagers and recognized for its love-themed songs. With words that are simple and easy to understand, their songs are not only fun to listen to, but they also change how people think about romantic relationships, especially now that digital platforms like TikTok, Spotify, and YouTube are so popular.  The study used a quantitative approach and a survey method, sending questions to 30 people who had listened to JKT48 songs.  Hastuti (2015) suggested some ways to measure the lyric variable, and West and Turner (2018) gave us ideas for how to measure the view of romantic relationships.  We used simple linear regression, t-tests, the coefficient of determination, and tests for normality, validity, and reliability to look at the data.  The results show that JKT48's songs have a big effect on how people think about relationships.  As you can see, the t-value of 6.445 is higher than 2.048, which means that the alternative hypothesis (Ha) is more likely to be true.  59.7% of the variation in romantic relationship impression (Y) can be explained by the lyric variable (X). The other 40.3% is due to factors outside of this study.   Keywords: Fortune Cookie Yang Mencinta, Romantic Relationships, JKT48, Banjarbaru